2018
DOI: 10.1029/2017jd027977
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the MJO and North Pacific Storm Track Relationship by the QBO

Abstract: This study demonstrates a possible impact of the quasi‐biennial oscillation (QBO) on the Madden‐Julian Oscillation (MJO)‐related North Pacific storm track (NPST) change during October–March for the period of 1979–2016. The NPST shows significant intraseasonal changes in response to the MJO. In general, when the MJO convection is located over the Indian Ocean (western to central Pacific), the NPST tends to shift poleward (southward). This MJO‐related NPST change has larger amplitude during the easterly phase of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 74 publications
(118 reference statements)
1
46
0
Order By: Relevance
“…The CESM simulation results also show similar stronger poleward Plumb flux transport over Eurasia in February during EQBO phases (Figure d), although this phenomenon is not quite the same in January (Figure c). The enhanced poleward propagation of synoptic‐scale waves in late winter might be related to the poleward shift of the subtropical jet during EQBO phases (i.e., positive wind contour lines to the north of 30°N over Asia in Figure and positive zonal wind anomalies to the north of 30°N in Figure ), which is in agreement with previous findings (Lachmy & Harnik, ; Wang et al, ; White et al, ).…”
Section: Mechanisms Responsible For Qbo‐induced Polar Vortex Shiftmentioning
confidence: 99%
“…The CESM simulation results also show similar stronger poleward Plumb flux transport over Eurasia in February during EQBO phases (Figure d), although this phenomenon is not quite the same in January (Figure c). The enhanced poleward propagation of synoptic‐scale waves in late winter might be related to the poleward shift of the subtropical jet during EQBO phases (i.e., positive wind contour lines to the north of 30°N over Asia in Figure and positive zonal wind anomalies to the north of 30°N in Figure ), which is in agreement with previous findings (Lachmy & Harnik, ; Wang et al, ; White et al, ).…”
Section: Mechanisms Responsible For Qbo‐induced Polar Vortex Shiftmentioning
confidence: 99%
“…In westerly QBO, more planetary waves propagate into the tropics, and the poleward propagation is weaker, leading to a stronger polar vortex [27,34,35]. Both the MJO and the QBO can influence the atmospheric rivers, mid-latitude storm track, and extratropical climate [36][37][38][39].A recent study by Feng and Lin [40] indicated that the North Atlantic Oscillation (NAO) and the MJO connection can be modulated by the QBO. The positive NAO follows the MJO convection over the tropical Indian Ocean, and negative NAO is led by the MJO convection over the western Pacific [41,42].…”
mentioning
confidence: 99%
“…Such wave propagation typically occurs over the North Pacific (Figures a–d). Although this wave train is sensitive to the QBO (Son et al, ; Wang et al, ), its difference between EQBO and WQBO winters is mainly observed around the date line far downstream of the continent. This location may imply that the differences in precipitation anomalies (Figure and Table ) are mostly due to changes in the Rossby gyres response over the continent rather than to the wave train in the North Pacific modulated directly by the QBO.…”
Section: Resultsmentioning
confidence: 99%
“…Through this wave train, the MJO generates anomalous circulation in the extratropics that resembles the Pacific/North American pattern (Wallace & Gutzler, ; Zhang, ). This affects surface weather in the northern extratropics, including East Asia (EA; Jeong et al, ; Seo et al, ; Wang et al, ), North America (Bond & Vecchi, ), Europe (Seo et al, ), and even the Arctic (Yoo et al, ). Given this teleconnection, the MJO is considered as one of the key sources for subseasonal prediction in the extratropics (Vitart & Robertson, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation